STURGE WEBER SYNDROME-UNUSUAL PRESENTATION - Neki, N.S. (Journal of Ayub Medical College Abbottabad, 2014)
Sturge Weber Syndrome or encephalo-trigeminal angiomatosis is non-hereditary, congenital and rare disorder of unknown aetiology. It is characterised by vascular malformation with capillary venous angiomas involving face, eye and leptomeninges resulting in neurological and orbital manifestations. A case of 23 years old female presented with history of tonic-clonic convulsions, evidence of Port wine stain on face since birth, characteristic CT findings diagnosed as a case of Sturge Weber Syndrome is reported here for its rarity. Keywords: Sturge Weber Syndrome; Port -wine stain; Seizures